1994
DOI: 10.1038/sc.1994.115
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of spinal cord injuries: a reflection of changes in South African society

Abstract: The records of all patients (492 males and 124 females) admitted into a spinal rehabilitation programme over a period of 6 years were reviewed. Most of the patients were in the age group 20-29 years and trauma accounted for 89% of all spinal cord lesions. Gunshot injuries were the commonest (36%), followed by injuries related to motor vehicle accidents (MYA) (25%), stab wounds (20%) and falls from heights (2.4%). Aetiological patterns changed over the 6 year period covered: gunshot injuries increased markedly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 6 publications
5
45
0
2
Order By: Relevance
“…[71][72][73] Violence-related TSCI occurs in regions of conflict or high availability of weapons (gunshot wounds and stabbings). 7,46,74 The Maps reveal a band of violence through North and South America into Southern Africa and the Middle East. High rates of gunshot injuries are present in the USA and Brazil and the world's highest proportion in the country of South Africa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[71][72][73] Violence-related TSCI occurs in regions of conflict or high availability of weapons (gunshot wounds and stabbings). 7,46,74 The Maps reveal a band of violence through North and South America into Southern Africa and the Middle East. High rates of gunshot injuries are present in the USA and Brazil and the world's highest proportion in the country of South Africa.…”
Section: Discussionmentioning
confidence: 99%
“…High rates of gunshot injuries are present in the USA and Brazil and the world's highest proportion in the country of South Africa. 46,51,74,75 Greenland (Western Europe) also has a high proportion of violence (self-harm), causing TSCI with high rates of attempted suicide. 14 High suicide rates seem to predominate in Scandinavian countries.…”
Section: Discussionmentioning
confidence: 99%
“…18 In low-and middle-income countries, paraplegia seems to be more common (52-95%), 1,4 which is also reported from Sub-Saharan Africa (70-75%). 5,8 This might be explained by high prehospital mortality with cervical injuries. C1-4 were the most common levels of injury, most likely contributing to the high in-hospital mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 In our study, stabbing was the primary form of violence, with only one gunshot injury. Previous studies from low-or middle-income countries have shown that fall injuries result predominantly from falling from trees or roofs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation